Aegean Sea Issue Urgency on Maritime Jurisdiction and Territorial water extension between Turkey and Greece - Tobias Binsar (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
The Aegean sea issue is a long case that first occurred in 1950, the main issue of this case revolves on the geographical condition that has led Turkey and Greece on fighting over supremacy to take control of the Aegean sea area. The issue of both Turkey and Greece has earlier been submitted to the ICJ however, its lack of jurisdiction causes the issue itself to remain unresolved. In 2020 Greece has stated that they are looking forward to extending their territorial waters, the statement itself might become a big issue for Turkey and has further proved the urgency of actual maritime jurisdiction and real resolution towards the Aegean sea issue. The goal of this research is to clarify and find a resolution that can be used under the situation of the Aegean sea issue in both international legal theory and practice. Apart from giving clarification of possible and available Legal instruments and theories, this research will also elaborate even further on why Territorial water extension by Greece would call for an urgency, especially for Turkey. This research revealed that UNCLOS as an International law instrument still have some issues in practice of a unique circumstances issue like the Aegean Sea, and shows that in its practice both Turkey and Greece must have a good will intention to fully resolve the issue of Aegean sea to draw an end line to the long lasting issue of maritime jurisdiction over its territorial sea.